Flame-made nanoparticles for magnetic hyperthermia and MRI in colorectal cancer theranostics - Zhang, Yuming; Paraskeva, Christina; Chen, Qianying; Maisuradze, Anano; Ansari, Shaquib Rahman; Sarkar, Tapati; Koliaraki, Vasiliki; Teleki, Alexandra (Uppsala University, 2025)
Magnetic hyperthermia therapy using superparamagnetic iron oxide nanoparticles (SPIONs) offers a promising strategy for treating cancers resistant to chemo- and radiotherapy. However, oral delivery of SPIONs for localized treatment of gastrointestinal cancers has not been widely explored. Here, we report the development of methoxy polyethylene glycol (mPEG) functionalized SPIONs (mPEG-Mn0.6Zn0.4Fe2O4) engineered for oral administration with combined theranostic functionalities for magnetic hyperthermia treatment and magnetic resonance imaging (MRI) in colorectal cancer (CRC). The SPIONs achieved consistent heating performance in biorelevant colonic environments, exceeding a 5 °C temperature increase within 10 min under an alternating magnetic field (AMF). They also demonstrated superior r2 relaxivity compared to γ-Fe2O3, highlighting their potential as effective T2 MRI contrast agents. In vitro studies using CRC SW480 and Caco-2 cell lines assessed nanoparticle cytotoxicity, cellular uptake, and magnetic hyperthermia efficacy in both upright and inverted cell culture configurations. Magnetic hyperthermia induced significant CRC cell death in vitro, particularly in upright configurations, attributed to enhanced localized heating caused by nanoparticle sedimentation and enhanced SPION contact with cell surfaces. This emphasizes the importance of in vitro experimental parameters such as cell line, configuration, and AMF exposure time for systematic optimization of theranostic SPIONs during preclinical development. Finally, in vivo studies using a colorectal tumor xenograft mouse model demonstrated a marked therapeutic effect of magnetic hyperthermia by intratumorally injected SPIONs. The tumor volume was reduced by 63% following a single 20-minute AMF exposure. These findings demonstrate the potential of mPEG-Mn0.6Zn0.4Fe2O4 nanoparticles as a promising platform for non-invasive, image-guided magnetic hyperthermia therapy in CRC theranostics.
Keywords: Nanomedicine; Pharmaceutical sciences; Cancer therapy (excl. chemotherapy and radiation therapy); Cancer diagnosis; Nanomaterials; Nanoscale characterisation; Medical and Health Sciences; Medicin och hälsovetenskap; Nanotechnology for Materials Science; Nanoteknisk materialvetenskap; Cancer and Oncology; Cancer och onkologi; Pharmaceutical Sciences; Farmaceutiska vetenskaper